Porous Nickel Nano‐Foam by Femtosecond Laser Structuring for Supercapacitor Application. Issue 23 (15th October 2018) - Lange, Karsten; Hördemann, Christian; Schulz‐Ruhtenberg, Malte; Caro, Jürgen
Abstract: A focused femtosecond laser beam was scanned across a nickel electrode in a line pattern with different line distances to generate a large electrochemical surface area for charge storage. During the laser structuring process, small metal particles were generated and sintered to a porous foam‐like structure, the so‐called laser‐induced nano‐foam (LINF), which strongly adheres to the substrate surface. The structuring was carried out in argon atmosphere, in order to prevent oxidation of the LINF structure during the structuring process. The topography of the LINF was investigated by scanning electron microscopy and laser scanning microscopy. The electrochemical surface area of the electrodes was determined by cyclic voltammetry based on the charging of the double‐layer. The total capacity of the nickel LINF electrodes was measured by galvanostatic charge‐discharge to test their capability for supercapacitor applications. The surface area enlargement and therefore the total capacity increases with decreasing line distance. The LINF structure provides a surface area enlargement up to a factor of 1600 and a total capacity up to 2 C cm −2 . Abstract : Boosting capacity by femtosecond laser pulses: utilizing a femtosecond laser, a metallic porous surface structure, a so‐called laser‐induced nano‐foam (LINF), is fabricated under argon atmosphere. The LINF arrays on Ni substrate are created with the objective to generate electrodes showing a highly accessible surface area for electrochemical charge storage. The electrochemical surface area found is enlarged by a factor of 1600, demonstrating the great potential of this technique.